Data for: Simulating effects of agricultural intensification and climate change: Nitrogen fertilization and drought stress decrease insect herbivore performance - Raharivololoniaina, Ange; Moewert, Ellen; Fischer, Klaus (Dryad, 2022)
Biodiversity is globally under pressure, and the current decline in insect
biomass and diversity is likely caused by human activities. Key drivers of
biodiversity loss include agricultural intensification and anthropogenic
climate change. Nevertheless, a thorough understanding of potential
interactions between both factors and the mechanisms underlying insect
declines in general is still lacking. Here, we investigate the combined
effects of nitrogen fertilization and drought, as applied to host plants,
on the preference and performance of the butterfly Lycaena tityrus.
Individuals performed best on plants having received medium nitrogen
levels, while performance was reduced by either a lack of or strong
fertilization, the former potentially caused by nitrogen limitation and
the latter by increased concentrations of toxic allelochemicals. Female
oviposition preference though was positively related to nitrogen
fertilization, resulting in a mismatch between preference and offspring
performance at high nitrogen levels. Plant drought stress additionally
reduced herbivore performance, and females appeared to suffer more from
low-quality food than males. Our results indicate that increasing nitrogen
fertilization, as applied in intensive agriculture, may substantially
reduce host-plant quality for insect herbivores, which may be exaggerated
in the course of climate change due to the more frequent occurrence of
droughts. Our study thus contributes to a better understanding of the
mechanisms underlying human-driven insect declines in agricultural
landscapes and beyond.
Keywords: FOS: Biological sciences; extreme weather event; host-plant quality; Insect decline; land use practices; nitrogen limitation; Preference-performance hypothesis